The Influence of Guided Discovery Model with The Respiratory System Practicum on The Students' Learning Outcomes and Conservation Attitudes - Lupitasari, Laksita; Iswari, Retno Sri; Lisdiana, Lisdiana (Journal of Biology Education, 2021)
This research purpose is to find out the application of Guided Discovery model with the pratice material learning system to the learning outcomes and character of junior high school students. This research belongs to quasi experimental research with nonequivalent control group design. Population includes all students of class VIIIA to VIII of SMP Negeri 1 Watukumpul with VIIIB class as an experiment class and VIIIA as control class determined by purposive sampling. The t test results showed a significant posttest average differences between the experimental and control classes. The improvement found on 31 students in experimental class (medium-high), while only 18 students in control class have improved (medium-high). The highest average of experimental class found on the honest character which is 89.10, while 78.92 for the environmental care and 78.39 for the aspect of responsibility, better than the control class which is 78.00 for honest character, the environmental care is 76, 38, and the character of responsibility is 80.09. That findings showed the Guided Discovery model give the positive learning outcomes and student conservation characters. It is well supported by students and teachers on the application of the Guided Discovery model on the teaching of the respiratory system.